A method for difference cloning: gene amplification following subtractive hybridization. - Wieland, I (1990)
We describe a procedure for genomic difference cloning, a method for isolating sequences present in one genomic DNA population ("tester") that is absent in another ("driver"). By subtractive hybridization, a large excess of driver is used to remove sequences common to a biotinylated tester, enriching the "target" sequences that are unique to the tester. After repeated subtractive hybridization cycles, tester is separated from driver by avidin/biotin affinity chromatography, and single-stranded target is amplified by the polymerase chain reaction, rendering it double-stranded and clonable. We model two situations: the gain of sequences that result from infection with a pathogen and the loss of sequences that result from a large hemizygous deletion. We obtain 100- to 700-fold enrichment of target sequences.